Bringing Archaeology to the Public: A Kingston Viewpoint - Bazely, Susan M. (2006)
Kingston's past is rich in historical detail, whether it be architectural, political or archaeological. The staff of the Cataraqui Archaeological Research Foundation has drawn upon the archaeological collections from a variety of excavations, and Kingston's museum community to develop public access to the history and archaeology of the area. In addition to school workshops, the Foundation provides a well established summer archaeology program, and utilizes a variety of methods to bring archaeology to the public. These efforts have exposed both the process of archaeology, and an insight into the past, to the public.